2021
DOI: 10.3168/jds.2020-19388
|View full text |Cite
|
Sign up to set email alerts
|

Morphology, adipocyte size, and fatty acid analysis of dairy cattle digital cushions, and the effect of body condition score and age

Abstract: The digital cushion is an essential part of maintaining a healthy foot, working to dissipate foot strike and body weight forces and lameness from claw horn disruption lesions. Despite the importance of the digital cushion, little is known about the basic anatomy, adipocyte morphology, and fatty acid composition in relation to age, limb position, and body condition score. In total, 60 claws (from 17 cows) were selected and collected from a herd, ensuring that body condition score data and computed micro-tomogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…During periods of excessive weight loss, fat is mobilised from the digital cushion that hence loses much of its force dissipating capacities. Cows may develop impaired mobility as the decreasing dimensions of the digital cushion lead to increased pressures exerted on the corium, the germinative epithelium and the distal phalanx which promotes the development of traumatic claw lesions [87,88]. This reasoning is further underscored by our result that overconditioned cows experienced 0.77 times lower odds for a higher LS compared with animals in optimal condition.…”
Section: Plos Onementioning
confidence: 66%
“…During periods of excessive weight loss, fat is mobilised from the digital cushion that hence loses much of its force dissipating capacities. Cows may develop impaired mobility as the decreasing dimensions of the digital cushion lead to increased pressures exerted on the corium, the germinative epithelium and the distal phalanx which promotes the development of traumatic claw lesions [87,88]. This reasoning is further underscored by our result that overconditioned cows experienced 0.77 times lower odds for a higher LS compared with animals in optimal condition.…”
Section: Plos Onementioning
confidence: 66%
“…7,25 A recent postmortem study of digital cushion tissue found that cows with BCS > 3.0 at slaughter had significantly greater adipose cell size than cows with BCS < 2.5. 57 Another possible explanation for our BCS findings is that cows that develop SU in early lactation are likely to mobilise more fat due to the pain they experience and the associated reduced dry matter intake.…”
Section: Discussionmentioning
confidence: 94%
“…Low BCS and loss of BCS through lactation is known to be a risk factor for formation of claw horn disruption lesions and there is evidence that this is related to the thickness of the digital cushion 7,25 . A recent postmortem study of digital cushion tissue found that cows with BCS > 3.0 at slaughter had significantly greater adipose cell size than cows with BCS < 2.5 57 . Another possible explanation for our BCS findings is that cows that develop SU in early lactation are likely to mobilise more fat due to the pain they experience and the associated reduced dry matter intake.…”
Section: Discussionmentioning
confidence: 99%
“…Arachidic acid (20:0) is a SFA whose concentration differs between bovine tissues such as muscle and kidney adipose tissue 45 47 . In the study of Newsome et al 45 investigating the digital cushion of dairy cows, adipocytes size and concentration of arachidic acid were positively related to BCS. In the present study, the two groups did not differ in BCS.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the two groups did not differ in BCS. However, the NEB induces fat mobilization from functional fat reserves such as the digital cushion 45 . The reduction of arachidic acid in hyperketonemic group may be related to an increase of β-oxidation induced by palmitoleic and vaccenic acids.…”
Section: Discussionmentioning
confidence: 99%